Estudio de factibilidad para el cultivo de palma africana en la hacienda la tormenta, cantón Palenque, año 2014. - Castro Peralta, Viviana Elizabeth (2015)
In recent years shown moderate and sustained growth in the production of the fruit of the oil palm, to the point that outperforms traditional banana growing, because it goes beyond the 280 thousand hectares, settled in the provinces of Esmeraldas, Guayas, Los Ríos, and the Amazonian Orellana and Sucumbíos. Its momentum is largely due to their marketing has been smooth and safe, profitable prices for producers, even though they have continued to negatively affect nutritional and plant protection, problems which have been successfully controlled. The cultivation of African Palm promotes important investments, creates jobs and promotes the progress of extensive areas, not only for this perennial oleaginous crop, but the business generated around it. According to the National Association of growers of African Palm (ANCUPA), in this agricultural activity are employed directly around 60,000 people and it is estimated that in the business related to this crop as the commercialization and industrialization has been generated in addition 30,000 jobs. For these reasons was the initiative of carrying out a feasibility study for the cultivation of African Palm in the Canton Palenque province of Los Ríos in order to improve the economy of investors, generating work taking advantage of the benefits of climate and soil of the sector. Through this proposal, the requirements of market, technical and financial enabling to identify the feasibility of venture in the cultivation of oil palm fruit are determined.